A new methodology to identify and quantify material resource at a large scale for earth construction – Application to cob in Brittany. (10th May 2018) - Hamard, Erwan; Lemercier, Blandine; Cazacliu, Bogdan; Razakamanantsoa, Andry; Morel, Jean-Claude
Highlights: Proposed methodology is based on cross-referencing of spatialized pedological and heritage data. The earthwork waste reuse capacity for earth construction is estimated at regional scale. The first map of earth construction material availability at regional scale is proposed. Five texture classes of suitability for cob soils are defined for Brittany. Texture results call into question recommendations available in the literature. Abstract: A new methodology based on the cross-referencing of spatialized pedological and heritage data is proposed to identify and quantify soil resources available for earth construction. The paper underlines the pedological particularities of areas containing earth heritage and uses these particularities to propose criteria to assess the suitability of soils for modern earth construction. The methodology applied at the regional scale in France (for a given area of 27, 200 km 2 in Brittany) enabled to specify five new texture classes (balance between clay, silt, sand and gravel content) of suitability for cob soils. This result calls into question recommendations available in the literature. The methodology also provides data on the scale of availability of the resource to repair earth built heritage (cob) or to build new low impact buildings with integrated modern cob walls. In the studied area the potential waste recovery of 2.8 Mt per year is measured, highlighting the large availability of materials for earth construction. At least 23% of earthwork wastes of Brittany are suitable for earth construction (0.7 Mt). However, earth remains a non-renewable material and this resource has to be properly managed, requiring an appropriate building design and maintenance in order to increase longevity and to avoid the use of admixture, preventing earth reversibility at end of life.